(untitled) (Global Journal of Medical Research, 2023)
Early and accurate detection of cognitive decline is a crucial factor for diagnosis early interventions and treatment strategies The CLOX an executive clock drawing task has emerged as a useful and frequent method for assessing cognitive abilities especially in executive functioning domains However there are few normative data available for this tool This protocol translates and validates the CLOX an executive drawing task in the Greek population also it tries to examine the use of CLOX in the Greek population The study included a total number of participants 283 76 males- 207 females with mean ages 52 7 years and a range of 19 to 90 years the cohort consists of individuals with Dementia Multiple Sclerosis Systemic Lupus Erythematosus and Mild Cognitive Impairment The Internal consistency with a Cronbach s alpha value was 798 for CLOX task 1 785 for CLOX task 2 and 874 for the overall scale combining both tasks